PENGEMBANGAN MEDIA KARTU DOMINO BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Nurhamidah Sopyan, Azkiya; Bramianto Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem-solving abilities of fourth-grade elementary school students at SDN Mekarmukti 01 are still relatively low due to the lack of engaging and interactive learning media. This study aims to develop a learning media in the form of Domino Cards based on Education for Sustainable Development (ESD) to improve elementary school students' problem-solving abilities in the multiplication of whole numbers topic in fourth-grade elementary school. This study used the Research and Development (R&D) method with the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. The research instrument included a validation questionnaire from media experts with a score of 1.00, from material experts with a score of 1.00, and from language experts with a score of 1.00, categorizing it as "very good" or suitable for use in ESD-based mathematics learning on whole number multiplication in fourth-grade elementary school.